2020
DOI: 10.52584/qrj.1802.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugarcane Bagasse Ash as Partial Cement Replacement on the Compressive Strength of Concrete

Abstract: The disposal of solid waste in open environment is a serious alarming concern that needs immediate attention from the researchers. The hazardous solid agro-industrial wastes which include: wheat straw ash, rice husk ash, corn cob ash and sugarcane bagasse ash (SCBA), having pozzolanic properties, have a versatile use in concrete. The solid pozzolana enhances the various concrete properties by the reaction of silicates with calcium hydroxide in the presence of water, which in result generate a saturated zone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Similar observations were reported in the previous research studies, wherein SCBA addition resulted in a decrease in the slump of GGBFS based alkali‐activated concrete 86 . Apart from angular SCBA particles, higher water absorption capacity of SCBA has been consistently reported in the literature, which reduces the amount of water available to attain desired slump at constant water to binder ratio, thus lowering the workability 87,88 . It has also been reported that the decrease in slump could be attributed to the high specific surface area that reduces the flowability of the SCBA‐based concrete 89 .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Similar observations were reported in the previous research studies, wherein SCBA addition resulted in a decrease in the slump of GGBFS based alkali‐activated concrete 86 . Apart from angular SCBA particles, higher water absorption capacity of SCBA has been consistently reported in the literature, which reduces the amount of water available to attain desired slump at constant water to binder ratio, thus lowering the workability 87,88 . It has also been reported that the decrease in slump could be attributed to the high specific surface area that reduces the flowability of the SCBA‐based concrete 89 .…”
Section: Resultssupporting
confidence: 85%
“…86 Apart from angular SCBA particles, higher water absorption capacity of SCBA has been consistently reported in the literature, which reduces the amount of water available to attain desired slump at constant water to binder ratio, thus lowering the workability. 87,88 It has also been reported that the decrease in slump could be attributed to the high specific surface area that reduces the flowability of the SCBA-based concrete. 89 The differences in the impacts of CCA and SCBA on workability are due to their porosity and microstructure.…”
Section: Workability Using Slump Testmentioning
confidence: 99%
“…It is known that SBA contain amorphous SiO 2 , which acts as a puzzolana reacting with Ca(OH) 2 produced during the hydration process of cement and water, acting as a retarding reaction, resulting into the generation of a saturated zone of calcium silicate hydrate (CSH) gel, selling porous and increasing compression resistance. This CSH gel reduces the amount of calcium hydroxide Ca(OH) 2 and consequently the pH of the cementitious paste [ 75 ]. Metakaolin (MK), Al 2 Si 2 O 7 , is a highly amorphous dehydration product of kaolinite, Al 2 (OH) 4 Si 2 O 5 ; it contains silica and alumina in an active form which will react with CH.…”
Section: Resultsmentioning
confidence: 99%
“…Sugarcane bagasse ash (SCBA) produced from cane sugar can also be used to replace a portion of cement in concrete. Moreover, the substitution of 10% of cement by SCBA increased the compressive strength of concrete by 15.67% [26].…”
Section: Research Objectivesmentioning
confidence: 96%